2016
DOI: 10.9745/ghsp-d-16-00062
|View full text |Cite
|
Sign up to set email alerts
|

Using Qualitative Methods to Validate and Contextualize Quantitative Findings: A Case Study of Research on Sexual Behavior and Gender-Based Violence Among Young Swazi Women

Abstract: Nesting qualitative data collection methods within quantitative studies improves results by assessing validity and providing depth and context. Using data from 3 sources from Swaziland, we triangulate qualitative and quantitative findings to highlight how different methodologies produce discrepant data regarding risky sexual behaviors among young women. We found that women reported similar numbers of lifetime sex partners in all sources, but the proportion reporting multiple and concurrent partnerships was sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…QIs were used to contextualize quantitative data and provide insight into the feasibility of the intervention with caregivers. This process triangulates findings by ensuring that the results presented by researchers are in line with the participants' experiences (Ruark & Fielding‐Miller, ). Summative content analysis was chosen for the analysis as it allowed a presentation of content related to participants' perception of the interventions (Hsieh & Shannon, ).…”
Section: Methodsmentioning
confidence: 91%
“…QIs were used to contextualize quantitative data and provide insight into the feasibility of the intervention with caregivers. This process triangulates findings by ensuring that the results presented by researchers are in line with the participants' experiences (Ruark & Fielding‐Miller, ). Summative content analysis was chosen for the analysis as it allowed a presentation of content related to participants' perception of the interventions (Hsieh & Shannon, ).…”
Section: Methodsmentioning
confidence: 91%
“…We note too that this study used face-to-face interviews. While there has been some suggestion that computer-assisted self-interviews (which theoretically provide greater privacy) might yield more accurate data on sensitive behaviors [89], a meta-analysis of 15 studies in LMIC did not find evidence that the newer technology increased reporting of sexual behavior [90]. In Malawi specifically, a previous longitudinal study of adolescents found that that face-to-face interviewing produced more consistent reporting on sexual behaviors compared to computerassisted self-interviews [91].…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…The authors utilized a qualitative research methodology in conducting the research. As explained by Ruark & Fielding-Miller (2016) a qualitative methodology is beneficial for the researchers to obtain the data comprehensively and produce an in-depth analysis. Further on, they can gain the detailed information by interpreting the data from observations (Rahman, 2016).…”
Section: Methodsmentioning
confidence: 99%